The use of salivary glucose concentration as an indicator for glycemic control in diabetic patients in Benghazi - A. F. Ben Saod, Loai; A Sultan, Azzam (Libyan Journal of Dentistry, 2017)
Objectives: The aim of this study was to evaluate saliva glucose in diabetics and healthy people and assess the possibility of using salivary glucose concentration (SGC) for monitoring glycemic control instead of glycated hemoglobin (HbA1c). Subjects and Methods: The groups of study composed of: diabetic group consisted of 52 diabetic patients and 25 healthy subjects as a control group. After collection of saliva and blood samples, the SGC and fasting blood sugar (FBS) levels were measured with enzymatic-oxygen rate method by Beckman Glucose Analyzer II. HbA1c was measured by Cobas c 111- Roche.co. Independent samples t-test was used for the comparison of means. Pearson's r correlation coefficient was used to describe the magnitude and direction of the relationship. ANOVA (F test) and t-test were used to confirm the statistical significance and calculating the regression equation. Results: The average of SGC in diabetic group was significantly higher than non-diabetic group, 17.14 ± 4.69 mg/dl and 14.08 ± 1.63 mg/dl, respectively, with (p= 0.000). There was no significant correlation in diabetic and non-diabetic groups between SGC and HbA1c (p>0.05). We observed a significant correlation between FBS and HbA1c in diabetics (p<0.05). Conclusion: In this study, all salivary samples reflected presence of glucose in both groups. The average of SGC levels in diabetic group was significantly higher than non-diabetic subjects. In diabetics, there were no effects on the average of SGC with the change of gender, age, type of therapy and duration of the disease. SGC levels were not directly influenced by change in HbA1c levels